A review of cryptographic algorithm recognition technology for binary code. Issue 1 (April 2021) - Zhao, Chenxia; Kang, Fei; Yang, Ju; Shu, Hui
Abstract: Aiming at the cryptographic algorithm that may be contained in the binary program, combined with existing research results, several cryptographic algorithm identification techniques are analyzed, including control flow graphs, data flow graphs, feature matching, selection of command statistical attributes, and semantic-based behavior analysis. The recognition effects of related technologies are discussed respectively.